2017
DOI: 10.1186/s13054-017-1660-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of urinary tissue inhibitor of metalloproteinase-2 and insulin-like growth factor binding protein 7 for acute kidney injury: a meta-analysis

Abstract: BackgroundTissue inhibitor of metalloproteinase-2 (TIMP-2) and insulin-like growth factor binding protein 7 (IGFBP7), inducers of G1 cell cycle arrest, are two recently discovered good biomarkers for early diagnosis of acute kidney injury (AKI). To obtain a more robust performance measurement, the present meta-analysis was performed, pooling existing studies.MethodsLiterature in the MEDLINE (via PubMed), Ovid, Embase, and Cochrane Library databases was systematically searched from inception to 12 October 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 52 publications
2
49
0
1
Order By: Relevance
“…Therefore, multiple studies have focused on early detection of renal damage in order to implement early intervention, and decrease morbidity and mortality of AKI . In a previous study, we confirmed the predictive values of tissue inhibitor of metalloproteinase‐2 (TIMP‐2) and insulin‐like growth factor binding protein 7 (IGFBP7) for AKI . However, the prognostic value of urinary [TIMP‐2]·[IGFBP7] in predicting the need for RRT and mortality remains unclear.…”
supporting
confidence: 55%
See 4 more Smart Citations
“…Therefore, multiple studies have focused on early detection of renal damage in order to implement early intervention, and decrease morbidity and mortality of AKI . In a previous study, we confirmed the predictive values of tissue inhibitor of metalloproteinase‐2 (TIMP‐2) and insulin‐like growth factor binding protein 7 (IGFBP7) for AKI . However, the prognostic value of urinary [TIMP‐2]·[IGFBP7] in predicting the need for RRT and mortality remains unclear.…”
supporting
confidence: 55%
“…The predictive value of urinary [TIMP‐2]·[IGFBP7] for AKI was discussed in our previous study . Further, Su Y also identified the diagnostic value of this parameter for AKI.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations